A New Ant-Friendly Aiouea (Lauraceae) From the Brazilian Atlantic Rainforest - Brotto, Marcelo Leandro; de Moraes, Pedro Luís Rodrigues [UNESP] (Wiley, 2025)
Aiouea is a genus of Lauraceae restricted to the New World with about 75 accepted species. In Brazil, there are about 32 species, 21 endemic to the country. Recent field work in southeastern Brazil, as well as a comprehensive study of herbarium collections, revealed a new species that we describe here as Aiouea myrmecophila. It is endemic to the Atlantic rainforest of Espírito Santo state and occurs between 800 and 1120 m along the Mantiqueira Mountain range. It is categorized as Endangered (EN) according to IUCN criteria. Its putative relationships with other species in the genus are discussed.
Keywords: biodiversity; Cinnamomum; Mantiqueira; Neotropics; Ocotea; plant taxonomy